Impact of Sustainable Energy Technologies, Government Governance and Environmental Taxes on Sustainable Energy Transition in E7 Countries: Fresh Evidence using CUP-FM CUP-BC Approach - Keong , Ooi Chee; Aldeehani, Talla M.; Alajlani, Sami E.; Sibghatullah, Amena; Pardaev, Jamshid (International Journal of Energy Economics and Policy, 2026)
The current study examines the effectiveness of sustainable energy technologies, governance and environmental taxes on energy transition using E7 countries data for the period 2006-2020. The study used CUP-FM and CUP-BC estimation techniques to assess the relationship between variables. Findings of the study reveal the positive association between constructs, suggesting that expansion of clean energy resources including solar & hydroelectric energy helps economies to experience sustainable energy transition as it ensures energy security. The significant relationship of government governance also suggests that governance indicators are crucial for energy transition. Moreover, the effective imposition of environmental taxes facilitates industries to shift toward sustainability while discouraging the reliance on non-renewable resources. Interestingly, the positive influence of industrialization, inflation and population growth indicate that although industrialization and population growth amplify the demand of energy consumption, however, when driving demand is paired with sustainable policies, it may result in green energy transition. In addition, findings also suggest that economies have an opportunity to capitalize on inflation-led pricing trends to boost energy diversification and advance sustainable opportunities.